Functionalised thermally induced phase separation (TIPS) microparticles enabled for “click” chemistry - Nogueira, João C. F. (Royal Society of Chemistry, 2020)

(untitled) (Org Biomol Chem)
Due to their homogeneity, tuneable properties, low cost and ease of manufacture, thermally induced phase separation (TIPS) polymeric microparticles are emerging as an exciting class of injectable device for the treatment of damaged tissue or complex diseases, such as cancer. However, relatively little work has explored enhancing surface functionalisation of this system. Herein, we present the functionalisation of TIPS microparticles with both small molecules and an antibody fragment of Herceptin™, via a heterobifunctional pyridazinedione linker capable of participating in SPAAC “click” chemistry, and compare it to the traditional method of preparing active-targeted microparticle systems, that is, physisorption of antibodies to the microparticle surface. Antigen-binding assays demonstrated that functionalisation of microparticles with Herceptin Fab, via a pyridazinedione linker, provided an enhanced avidity to HER2+ when compared to traditional physisorption methods.